PSYCHOLOGICAL ANALYSIS IN NOVEL “YOU’VE REACHED SAM” BY DUSTIN THAO - Puji Adi Pertiwi; Nia Kurniati; jovanka, Novalizcitra; Milatun khasanah; Riska Mauliana (English Teaching Journal and Research: Journal of English Education, Literature, And Linguistics, 2025)
This analysis delves into the psychological traits of the characters in Dustin Thao's novel, "You've Reached Sam. " Employing a literary psychology approach, the author artfully reveals the nuances of his characters. Our research will utilize a descriptive analysis grounded in Sigmund Freud's theories, aiming to uncover the deeper meanings embedded within the narrative. To achieve this, we will employ a qualitative descriptive method, which aligns seamlessly with our analytical objectives. By examining the characters in "You've Reached Sam," we hope to enhance public awareness regarding the significance of mental health, the importance of accepting life's circumstances, and the ability to manage emotions in social interactions. Ultimately, the primary goal of this analysis is to explore the development and transformations of each character, as well as to uncover the psychological depth present in "You've Reached Sam. "